THE EFFECT OF CONSUMERS’ BEHAVIOR AND PERCEIVED RISK ON PURCHASE DECISIONS AMONG ONLINE SHOP CONSUMERS - Dewi Indriani Jusuf; Dadang Munandar (Faculty of Economics and Business, University of Pasundan, 2021)
The goal of the research is to know the effect of the consumer behavior and perceived risk on, the consumers’ buying decision. This research employs a quantitative approach, descriptive and verified design. As much as 100 consumers are selected as respondents using a purposive method. The instrument of data collection is questionnaire. The data analysis used is Structural Equation Modeling. The research results show that the consumer behavior and perceived risk affects the consumer buying decision significantly. The biggest effect of the consumer behavior dimension on the buying decision variable is a personal factor and the biggest effect of the consumer behavior variable is on payment method dimension. The perceived risk contributes to the consumer buying decision significantly. It also proves that that the emerging of the online shops contributes shifting of the consumer behavior from a conventional business transaction into a digital one among the consumers.